Gene action and combining ability estimates for yield and other quantitative traits in chickpea (Cicer arietinum) - Bhardwaj, R; Sandhu, J S; Gupta, S K (The Indian Journal of Agricultural Sciences, 2011)
A diallel set of 6 parents and their 15 F1 hybrids were analyzed to understand the nature and magnitude of gene action and to identify the best combiners for yield and its component traits of chickpea (Cicer arietinum L.) The gca and sca components showed the predominance of additive gene action in governing days to flowering, days to poding, plant height, number of pods, number of seeds/pod, plant biomass, harvest index, grain yield and 100-seed weight and nonadditive gene action for number of branches. Estimates of gca effects showed that the parent ‘GL 98010’ was the best general combiner, followed by ‘GL 96010’ and ‘GL 90168’. Thus the ascochyta blight resistant parents ‘GL 96010’, ‘GL 98010’ and ‘GL 90168’ should be involved in the hybridization programmes for making yield breakthrough in chickpea. The cross combination ‘GL 98010’×‘GL 90168’ showed significant and desirable sca effects for most of the traits including grain yield.